2019
DOI: 10.1101/635516
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved epigenetic regulatory logic infers genes governing cell identity

Abstract: Understanding genetic control of cell diversification is essential for establishing mechanisms controlling biological complexity. This study demonstrates that the a priori deposition of H3K27me3 associated with gene repression across diverse cell states provides a genome-wide metric that enriches for genes governing fundamental mechanisms underlying biological complexity in differentiation, morphogenesis, and disease. We use this metric in combination with more than 1 million genome-wide data sets from diverse… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…We recognize that many of the DE genes are likely indirectly affected downstream targets and that key regulatory factors are commonly expressed at relatively low abundance. To enrich for the genes that have a strong potential to be cell identity genes, we implemented TRIAGE (transcriptional regulatory inference analysis from gene expression) 56 alongside the DE analysis. Of note, Gsx1, Gsx2, and Ascl1 were found among the most downregulated genes in the Elp2H206R developing brain (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recognize that many of the DE genes are likely indirectly affected downstream targets and that key regulatory factors are commonly expressed at relatively low abundance. To enrich for the genes that have a strong potential to be cell identity genes, we implemented TRIAGE (transcriptional regulatory inference analysis from gene expression) 56 alongside the DE analysis. Of note, Gsx1, Gsx2, and Ascl1 were found among the most downregulated genes in the Elp2H206R developing brain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating epigenetic repressive tendency to identify candidate genes in the transcriptome data. To narrow down a candidate gene set responsible for Elp2 mutant phenotypes, we incorporated the epigenetic repressive tendency score (RTS) into the conventional differential expression analysis output 56 . We calculated a metric that combined both significance of the DE analysis and regulatory importance of individual genes (i.e., pÀvalue from DE analysis repressive tentency score ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this study suggests that co-binding of OTX2 with either LHX1 or GSC likely determines activation or repression of OTX2 target genes, respectively, in Xenopus anterior development. SIX3, which in addition to anterior neural plate is expressed in hESCderived ME and in early mouse DE (Shim et al, 2020), may also be involved. It is induced, albeit at low levels, by TGF-β1 in our cells and has been shown to repress BMP and WNT ligand expression in anterior neural plate (Gestri et al, 2005;Lagutin et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that, by combining H3K27me3 ChIP-seq and RNA-seq profiling, the main regulators of the different cell types found within a heterogeneous population can be identified by those genes that, although highly expressed, are embedded within broad H3K27me3 domains (Rehimi et al, 2016; Schertel et al, 2015; Shim et al, 2020). Using this simple epigenomic approach to dissect epidermal SC heterogeneity, here we identified several putative regulators of non-bulge SCs.…”
Section: Introductionmentioning
confidence: 99%